KEUTAMAAN DALAM KARYA-KARYA KEMANUSIAAN YB. MANGUNWIJAYA - CB. Mulyatno (P3TK, Sanata Dharma University, 2013)
Yusuf Bilyarta Mangunwijaya (1929-1999) is well known as an Indonesian architect, writer, Catholic religious leader and social worker who help those who were poor, oppressed and marginalised by political system and policy. When he was sixteen, he joined the People's Security Army for defending Independency of Indenesia. Then he was aware of the important contritution of the villagers for achieving Indonesian independency. This awareness urges him to dedicate himself for serving others. As a priest, he served the people from various religions, especially the poor. What are the principal virtues of YB. Mangunwijaya? His principal virtues cover his writings and social concern. Therefore, the first step of this research is to represent the traces of his activities. Then, the following step is the analysis on his writings to reveal the main virtue that influences his life and activities. Love is the main vuritue that inspires Mangunwijaya to actualize justice, fraternity, solidarity and peace in the society.